Implementation Of Disaster Risk Reduction Policy In Indonesia - Indira Rachel; Muhamad Hidayat (Jurnal Ekonomi, 2024)
This research analyzes the implementation of Presidential Regulation (PERPRES) Number 87 of 2020 as a significant step in supporting the implementation of the Paris Agreement, Sustainable Development Goals (SDGs), and the Sendai Framework for Disaster Risk Reduction (SFDRR) in Indonesia. Although the PERPRES shows a strong commitment to these global goals, this research identifies several areas that require further attention to ensure the effectiveness of disaster risk reduction governance. The main focus of the research is on the PERPRES communication strategy, where there is potential to increase transparency, deepen information to the public, and strengthen public support through advocacy campaigns. In addition, this research highlights the evaluation of the success of PERPRES in formulating disaster management policies that are in line with the principles of the Paris Agreement, SDGs, and SFDRR. These findings underscore Indonesia's commitment to achieving adaptive and sustainable disaster management goals, in line with widely recognized global frameworks.